Method for producing coating ink composition, and lithium secondary battery for thermal runaway retardation comprising electrode coated with coating ink
The manufacturing of graphene ink compositions through thermal plasma and high-pressure homogeneity technology solves the problems of high cost and environmental pollution in the prior art, and delays the secondary battery on the electrode by coating graphene nanosheets or non-graphene oxide. Thermal runaway phenomenon has achieved environmentally friendly, low-cost and efficient battery safety improvement.
Patent Information
- Application Number
- CN202410449923.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-04
- Filing Date
- 2024-04-15
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art has problems such as high cost, environmental pollution and difficulty in mass production in manufacturing graphene ink compositions, and the endothermic additives cannot effectively prevent thermal runaway in the secondary battery.
Use expanded graphite as the starting material to make graphene nanosheets through hot plasma, and use shear stress of a high-pressure homogenizer to produce ink compositions for coating, avoid the use of acid chemicals, simplify the process to reduce costs and time, and at the same time Graphene nanosheets or non-graphene oxide are coated on the electrode to delay thermal runaway.
The environmentally friendly and low-cost graphene ink composition is realized, which improves the viscosity, dispersion stability and conductivity of the ink, and effectively delays and prevents thermal runaway in the secondary battery.
Smart Images

Figure CN119275292A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a coating ink composition and a lithium secondary battery for delaying thermal runaway, comprising an electrode coated with the coating ink produced by the production method. Background Art
[0002] Graphene is a two-dimensional allotrope composed of carbon atoms with a honeycomb hexagonal structure and a large specific surface area (about 2600m 2 / g) and theoretically 550Fg -1 Graphene is a material with excellent capacitance characteristics and physical and chemical stability. Graphene has unlimited application possibilities such as energy storage materials, transparent electrode films, barrier films, graphene / metal composites, and heat dissipation materials.
[0003] As a method for producing such graphene, there are graphene flakes (GF) produced by peeling graphene from graphite crystals and CVD (Chemical Vapor Deposition) graphene produced by a chemical vapor deposition method.
[0004] However, in the case of producing CVD graphene by chemical vapor deposition, large-area, high-quality graphene can be produced by gasifying carbon at high temperature and depositing it on a metal surface, but there are problems such as difficulty in mass production and difficulty in performing processes suitable for actual products.
[0005] In contrast, graphene sheets can be produced in large quantities at low cost, but their slightly reduced performance and low dispersibility limit the types of products they can be used in.
[0006] Therefore, as a technology for solving the above-mentioned problem, the technology disclosed in Patent Document 1 has been recently proposed.
[0007] Referring to the above-mentioned Patent Document 1, a graphene ink composition is disclosed, comprising chemically modified graphene, graphene sheets, a binder and a solvent, wherein the absolute value of the zeta potential of the charged chemically modified graphene is above 25 mV.
[0008] However, the above-mentioned patent document 1 includes the steps of exfoliating graphite oxide, chemically modifying the exfoliated graphene several times, and then further performing a step of mixing an adhesive and a solvent after separately manufacturing the first colloid and the second colloid to manufacture the ink composition. Therefore, the manufacturing cost and time are increased, and mass production is difficult. In addition, there is the problem of environmental pollution caused by the use of chemical substances such as acids and adhesives.
[0009] On the other hand, referring to the above-mentioned Patent Document 2, it discloses a secondary battery using an endothermic additive that improves the safety of the battery cell by absorbing heat when the secondary battery generates abnormal heat, and can prevent thermal runaway caused by abnormal use.
[0010] However, the above-mentioned Patent Document 2 has the inconvenience of additionally assembling an expansion material containing an endothermic additive into the electrode assembly in order to prevent or delay thermal runaway, and has the following problem: as an expansion material containing an endothermic additive for dispersing the heat energy generated in the secondary battery to the outside, it is impossible to substantially prevent thermal runaway occurring in the secondary battery.
[0011] Therefore, in order to solve the above problems, there is an urgent need for the following method: a method for producing a coating ink composition that uses expanded graphite (EG) as a starting material to obtain non-oxidized graphene, thereby eliminating the need for a reduction step and producing environmentally friendly non-oxidized graphene that does not cause environmental problems because no acid is used, thereby reducing the production cost and shortening the time through a simple production process and enabling mass production.
[0012] Furthermore, there is an urgent need for a method for producing an ink composition that delays and prevents thermal runaway caused by thermal overload in a secondary battery by coating a coating ink composition containing graphene nanosheets or non-oxidized graphene on an electrode of a secondary battery.
[0013] Prior Art Literature
[0014] Patent Literature
[0015] (Patent Document 0001) Patent Document 1: Korean Patent Publication No. 10-2018-0086676 (published on August 1, 2018)
[0016] (Patent Document 0002) Patent Document 2: Korean Patent Gazette No. 10-2331161 (published on November 22, 2021) Summary of the invention
[0017] Technical issues
[0018] The present invention aims to solve the above-mentioned problems and relates to a method for producing a coating ink composition and a lithium secondary battery for delaying thermal runaway including an electrode coated with the coating ink produced by the production method.
[0019] Technical Solution
[0020] In order to solve the above-mentioned problems, the present invention provides a method for producing a coating ink composition, characterized in that it comprises:
[0021] (a) Steps for producing graphene nanosheets using thermal plasma;
[0022] (b) a step of mixing and stirring a polymer in a solvent to produce a first polymer solution;
[0023] (c) a step of adding the manufactured graphene nanosheets into the manufactured first polymer solution to manufacture a first graphene solution;
[0024] (d) a step of subjecting the first graphene solution to high-speed homogenization to produce a second graphene solution; and
[0025] (e) A step of preparing a coating ink composition containing graphene nanosheets by using the second graphene solution using shear stress of a high-pressure homogenizer.
[0026] Furthermore, the present invention provides a method for producing a coating ink composition, characterized in that the average particle size of the graphene nanosheets is 0.1 μm to 100 μm.
[0027] Furthermore, the present invention provides a method for producing a coating ink composition, wherein the solvent is selected from one or more of water, an alcohol solvent including ethanol, chloroform, glycerol and acetic acid.
[0028] Furthermore, the present invention provides a method for producing a coating ink composition, characterized in that the polymer is selected from one or more of polyvinylpyrrolidone (PVP), polyvinyl alcohol (PVA), polyethylene glycol (PEG), polypropylene glycol (PPG), polyacrylo Nitrile (PAN) and polyacrylic acid (PAA).
[0029] Furthermore, the present invention provides a method for producing a coating ink composition, wherein the first polymer solution is obtained by mixing the solvent and the polymer at a mixing ratio of 95:5 or 5:1, respectively.
[0030] Furthermore, the present invention provides a method for producing a coating ink composition, characterized in that in the step (c), the graphene nanosheets added to the first polymer solution are added in an amount of 0.2 parts by weight to 20 parts by weight based on 100 parts by weight of the first polymer solution.
[0031] Furthermore, the present invention provides a method for producing a coating ink composition, characterized in that it also includes: (f) a step of producing graphene nanosheets using thermal plasma, and (g) a step of producing non-oxidized graphene powder by crushing the graphene nanosheets using an air jet mill.
[0032] Furthermore, the present invention provides a method for producing a coating ink composition, wherein the average particle size of the non-oxide graphene powder is 0.2 μm to 20 μm.
[0033] Furthermore, the present invention provides a coating ink produced by the method for producing the coating ink composition.
[0034] Furthermore, the present invention provides a method for coating a metal surface, characterized in that it comprises: the steps of coating the aforementioned coating ink on the metal surface; and
[0035] A step of forming a graphene coating film on the metal surface by drying or heat-treating the applied coating ink.
[0036] Furthermore, the present invention provides a method for coating a metal surface, characterized in that the step of coating the coating ink is performed by a coating method selected from dip coating, doctor-blade coating, slot-die coating and spray coating.
[0037] Furthermore, the present invention provides a method for coating a metal surface, characterized in that the step of forming the graphene coating film is drying at a temperature of 30°C to 100°C for 5 minutes to 30 minutes, or heat treating at a temperature of 100°C to 200°C for 10 minutes to 120 minutes.
[0038] Furthermore, the present invention provides a graphene-coated metal material, comprising: a metal material; and a graphene coating film coated on the surface of the metal material by the aforementioned method for coating a metal surface.
[0039] Furthermore, the present invention provides a lithium secondary battery, characterized by comprising an electrode having the coating ink coated on the surface of a current collector.
[0040] Furthermore, the present invention provides a lithium secondary battery, characterized in that the coated electrode is a positive electrode and / or a negative electrode.
[0041] Furthermore, the present invention provides a lithium secondary battery, characterized in that the lithium secondary battery is a lithium secondary battery for delaying thermal runaway.
[0042] Technical Effects
[0043] The method for producing the coating ink composition of the present invention does not require a reduction step because expanded graphite (EG) is used as a starting material to obtain non-oxidized graphene. Furthermore, since no acid is used, the manufacturing cost and manufacturing time can be reduced through a simple manufacturing process, and mass production can be achieved without causing environmental problems.
[0044] Furthermore, the coating ink composition produced by the method for producing a coating ink composition of the present invention uses a polymer as an additive, thereby improving ink properties such as viscosity, dispersion stability, conductivity, and substrate adhesion.
[0045] Furthermore, the coating ink composition produced by the method for producing a coating ink composition of the present invention is applied to an electrode of a secondary battery by coating the coating ink composition containing graphene nanosheets or non-oxidized graphene, thereby delaying and preventing thermal runaway caused by thermal energy overload in the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The accompanying drawings are used to explain the contents of the present invention in more detail to those skilled in the art, but the technical concept of the present invention is not limited thereto.
[0047] Figure 1 is a flow chart showing a method for manufacturing a coating ink composition using graphene nanosheets according to an embodiment of the present invention;
[0048] Figure 2 is a flow chart showing a method for preparing a coating ink composition using non-oxide graphene powder according to an embodiment of the present invention;
[0049] Figure 3 1 is a SEM (scanning electron microscope) image showing a graphene nanosheet manufactured by a method for manufacturing a coating ink composition according to one embodiment of the present invention;
[0050] Figure 4 1 is a SEM image showing non-oxidized graphene produced according to a method for producing a coating ink composition according to one embodiment of the present invention;
[0051] Figure 5 is a diagram showing an ink composition manufactured according to a method for manufacturing a non-oxide graphene ink composition for coating according to one embodiment of the present invention;
[0052] Figure 6 is a graph of an ink composition manufactured according to a method for manufacturing a coating ink composition according to one embodiment of the present invention measured by a stability analyzer (Turbiscan);
[0053] Figure 7is a graph comparing ink compositions manufactured according to a method for manufacturing a coating ink composition according to one embodiment of the present invention using a Brookfield viscometer;
[0054] Figure 8 The graph is a graph of the ink composition produced according to the method for producing an ink composition for coating according to one embodiment of the present invention measured by a stability analyzer (Turbiscan).
[0055] Description of Reference Numerals
[0056] 100: Method for producing coating ink composition containing graphene nanosheets
[0057] S110: Steps for making graphene nanosheets using thermal plasma
[0058] S120: step of mixing and stirring a polymer in a solvent to produce a first polymer solution
[0059] S130: a step of adding the manufactured graphene nanosheets into the manufactured first polymer solution to manufacture a first graphene solution
[0060] S140: a step of performing high-speed homogenization on the first graphene solution to produce a second graphene solution
[0061] S150: Using the shear stress of a high-pressure homogenizer to produce a coating ink composition containing graphene nanosheets from the second graphene solution. Step 200: Method for producing a coating ink composition containing non-oxidized graphene powder
[0062] S210: Steps for making graphene nanosheets using thermal plasma
[0063] S220: a step of crushing the graphene nanosheets by using an air jet mill to produce non-oxidized graphene powder DETAILED DESCRIPTION
[0064] Hereinafter, the method for producing the non-oxide graphene ink composition for coating of the present invention will be described in detail, but the protection scope of the method for producing the non-oxide graphene ink composition for coating is not limited to the following description.
[0065] When it is mentioned throughout the specification that a part “includes” a certain constituent element, unless there is any particular description to the contrary, it means that other constituent elements may also be included, rather than excluding other constituent elements.
[0066] Figure 1 1 is a flowchart showing a method 100 for producing a coating ink composition using graphene nanosheets according to an embodiment of the present invention.
[0067] Reference Figure 1 The method 100 for manufacturing a coating ink composition using graphene nanosheets of the present invention includes: (a) step S110 of manufacturing graphene nanosheets using thermal plasma, (b) step S120 of mixing and stirring a polymer in a solvent to manufacture a first polymer solution, (c) step S130 of adding the manufactured graphene nanosheets into the manufactured first polymer solution to manufacture a first graphene solution, (d) step S140 of high-speed homogenizing the first graphene solution to manufacture a second graphene solution, and (e) step S150 of manufacturing a coating ink composition containing graphene nanosheets through the second graphene solution using the shear stress of a high-pressure homogenizer.
[0068] Hereinafter, the method 100 for producing the non-oxide graphene ink composition for coating of the present invention will be described in detail.
[0069] [Production Example 1]
[0070] Reference Figure 1 and Figure 3 In step (a) of manufacturing graphene nanosheets using thermal plasma S110, expandable graphite (EG) is put into a thermal plasma device, and graphene is exfoliated by expansion caused by thermal plasma treatment, thereby obtaining graphene nanosheets.
[0071] The term "expanded graphite" in this specification may refer to a substance in which a sulfur or nitrogen compound is mixed with graphite to chemically expand the graphite. In this case, it may also refer to a substance in which the sulfur or nitrogen compound is used as an intercalating substance that penetrates between graphite layers, and graphite is exfoliated by interlayer penetration of the sulfur or nitrogen compound. In this form, the substance can further physically expand by applying energy.
[0072] The specific description of such expanded graphite (EG) is well known to those skilled in the art, and thus a detailed description thereof will be omitted.
[0073] The inventors of the present invention realize that when using graphite materials to exfoliate graphene, it is necessary to induce oxidation of the graphite surface, but the oxidation is mainly carried out using strong acids, which may cause environmental problems. In addition, when using the oxidized graphite, it needs to be reduced again after the graphene is manufactured in order to manifest its physical properties. Therefore, an additional process is required, making it difficult to continuously obtain a large amount of high-purity graphene.
[0074] Furthermore, as in the present invention, when graphene is peeled off from expanded graphite (EG), if the existing electrochemical peeling method, non-oxidative peeling method, graphene oxide reduction method and thermal expansion method are used to peel graphene from graphite, the carbon spaces sp in the graphite are2 The bonds are destroyed, and there is a problem that the physical properties of graphite, such as strength, thermal conductivity, and electron mobility, are significantly reduced, and the graphite needs to be discarded.
[0075] In this regard, the present inventors have confirmed that, as in the present invention, when expanded graphite (EG) is used, no strong acid is used, no environmental problems are caused, no additional reduction process is required, and there is no change in the physical properties of the expanded graphite (EG) after the graphene is peeled off from the expanded graphite (EG). Therefore, it is possible to obtain high-purity graphene that is recyclable and can be continuously used commercially, thereby completing the present invention.
[0076] Therefore, the method 100 for producing a coating ink composition according to one embodiment of the present invention requires the use of expanded graphite (EG) as a starting material.
[0077] However, when using such expanded graphite (EG), considering that the volume of the expanded graphite increases by more than 200 times when it is exfoliated into graphene, when a high-temperature box furnace or tunnel furnace is used to expand and exfoliate the expanded graphite (EG) in order to exfoliate into graphene, even if the volume of the furnace is large, only a few grams (g) of graphene can be obtained per hour, and the powder needs to be collected separately after the reaction, so continuous production is not possible, and there is a problem that it is difficult to quickly mass-produce commercially.
[0078] In view of this, the present inventors used thermal plasma to obtain graphene from the expandable graphite in order to continuously obtain high-purity graphene without performing an additional process, thereby solving the above-mentioned problem.
[0079] Figure 3 : is a SEM image showing graphene nanosheets produced by a method for producing a coating ink composition according to one embodiment of the present invention.
[0080] Reference Figure 3 The average particle size of the graphene nanosheets is 0.1 μm to 100 μm, preferably 0.2 μm to 70 μm, and more preferably 0.5 μm to 50 μm.
[0081] That is, according to the present invention, graphene nanosheets continuously produced from expanded graphite (EG) do not require a reduction step, can be obtained with very few impurities and high purity, and the obtained ink composition can also have excellent physical properties.
[0082] Thereafter, in step (b) S120 , a polymer is mixed and stirred in a solvent to produce a first polymer solution.
[0083] Among them, the solvent can be water, alcohol solvents including ethanol, chloroform, glycerol, acetic acid and other polar solvents. More specifically, one or more selected from acetone, methyl ethyl ketone, methanol, ethanol, isopropanol, butanol, ethylene glycol, ethylene glycol, polyethylene glycol, tetrahydrofuran, dimethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone, hexane, cyclohexanone, toluene, chloroform, distilled water, dichlorobenzene, xylene, trimethylbenzene, pyridine, methylnaphthalene, nitromethane, acrylonitrile, octadecylamine, aniline, dimethyl sulfoxide, dichloromethane, diethylene glycol methyl ethyl ether and ethyl acetate can be used.
[0084] Furthermore, the polymer may be one or more selected from the group consisting of polyvinylpyrrolidone (PVP), polyvinyl alcohol (PVA), polyethylene glycol (PEG), polypropylene glycol (PPG) and polyacrylic acid (PAA).
[0085] Here, the solvent and the polymer may be stirred in a mixing ratio of 85:15 parts by weight, preferably 90:10 parts by weight, more preferably 95:5 parts by weight, and may be stirred in a mixing ratio of 15:3 parts by weight, preferably 10:2 parts by weight, more preferably 5:1 parts by weight.
[0086] In the step (c) S130, the prepared graphene nanosheets are added to the prepared first polymer solution to prepare a first graphene solution.
[0087] More specifically, based on 100 parts by weight of the first polymer solution, the graphene nanosheets are added to the first polymer solution in a mixing ratio of 0.2 parts by weight to 20 parts by weight, preferably 0.5 parts by weight to 15 parts by weight, and more preferably 1 part by weight to 10 parts by weight to produce the first graphene solution.
[0088] Then, in the step (d) S140, the first graphene solution is subjected to high-speed homogenization to produce a second graphene solution.
[0089] Here, the first graphene solution is homogenized at high speed by a high-speed homogenizer, and the high-speed homogenizer can homogenize at a speed of 4000 rpm to 10000 rpm for 30 minutes to 60 minutes to obtain the second graphene solution.
[0090] More specifically, the graphene nanosheets contained in the first graphene solution are subjected to shear stress by passing through the nano units of the high-speed homogenizer, resulting in the graphite layers being peeled off in stages to obtain the second graphene solution.
[0091] Thereafter, in the step (e) S150, a coating ink composition containing graphene nanosheets is manufactured from the second graphene solution using the shear stress of a high-pressure homogenizer.
[0092] Here, the second graphene solution can be subjected to shear stress for 30 to 60 minutes under a pressure condition of 1000 to 2000 bar by the high-pressure homogenizer, and high-pressure homogenization can be repeated 3 to 10 times to prepare a coating ink composition containing graphene nanosheets.
[0093] [Production Example 2]
[0094] Figure 2 2 is a flow chart showing a method 200 for manufacturing a coating ink composition using non-graphene oxide powder according to an embodiment of the present invention.
[0095] Reference Figure 2 , and may further include (f) a step S210 of manufacturing graphene nanosheets using thermal plasma, and (g) a step S220 of manufacturing non-oxidized graphene powder by crushing the graphene nanosheets using an air jet mill.
[0096] More specifically, in the (g) step S220, the non-oxide graphene powder produced in the (b) step S120 is added to the first polymer solution to produce a first graphene solution.
[0097] Here, based on 100 parts by weight of the first polymer solution, the first polymer solution and the non-oxide graphene powder are mixed in a ratio of 0.05 parts by weight to 20 parts by weight, preferably 0.08 parts by weight to 14 parts by weight, and more preferably 0.1 parts by weight to 10 parts by weight to produce the first graphene solution.
[0098] More specifically, the non-graphene oxide powder has an average particle size of 0.2 μm to 20 μm, preferably a size of 1 μm to 10 μm.
[0099] Thereafter, in the (b) step S120 , a polymer is mixed and stirred in a solvent to produce a first polymer solution.
[0100] Among them, the solvent can be water, alcohol solvents including ethanol, chloroform, glycerol, acetic acid and other polar solvents. More specifically, one or more selected from acetone, methyl ethyl ketone, methanol, ethanol, isopropanol, butanol, ethylene glycol, ethylene glycol, polyethylene glycol, tetrahydrofuran, dimethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone, hexane, cyclohexanone, toluene, chloroform, distilled water, dichlorobenzene, xylene, trimethylbenzene, pyridine, methylnaphthalene, nitromethane, acrylonitrile, octadecylamine, aniline, dimethyl sulfoxide, dichloromethane, diethylene glycol methyl ethyl ether and ethyl acetate can be used.
[0101] Furthermore, the polymer may be one or more selected from polyvinylpyrrolidone (PVP), polyvinyl alcohol (PVA), polyethylene glycol (PEG), polypropylene glycol (PPG), polyacrylo Nitrile (PAN) and polyacrylic acid (PAA).
[0102] Here, the solvent and the polymer may be stirred in a mixing ratio of 85:15 parts by weight, preferably 90:10 parts by weight, more preferably 95:5 parts by weight, or in a mixing ratio of 15:3 parts by weight, preferably 10:2 parts by weight, more preferably 5:1 parts by weight.
[0103] In the (c) step S130, the non-oxide graphene powder prepared is added to the prepared first polymer solution to prepare a first graphene solution.
[0104] More specifically, based on 100 parts by weight of the first polymer solution, the non-oxide graphene powder is added to the first polymer solution in a mixing ratio of 0.2 parts by weight to 20 parts by weight, preferably 0.5 parts by weight to 15 parts by weight, and more preferably 1 part by weight to 10 parts by weight to manufacture the first graphene solution.
[0105] Then, in the step (d) S140, the first graphene solution is subjected to high-speed homogenization to produce a second graphene solution.
[0106] Here, the first graphene solution is homogenized at high speed by a high-speed homogenizer, and the high-speed homogenizer can perform high-speed homogenization at a speed of 4000 rpm to 10000 rpm for 30 minutes to 60 minutes to obtain the second graphene solution.
[0107] More specifically, the non-oxidized graphene powder contained in the first graphene solution is subjected to shear stress by passing through the nano-units of the high-speed homogenizer, resulting in the stepwise exfoliation of graphite layers to obtain the second graphene solution.
[0108] Thereafter, in the step (e) S150, a coating ink composition including non-oxide graphene powder is manufactured from the second graphene solution using the shear stress of a high-pressure homogenizer.
[0109] Here, the second graphene solution can be subjected to shear stress for 30 minutes to 60 minutes under a pressure condition of 1000 bar to 2000 bar by the high-pressure homogenizer, and high-pressure homogenization can be repeated 3 to 10 times to prepare a coating ink composition containing non-oxide graphene powder.
[0110] [Production Example 3]
[0111] A method (not shown) of coating a metal surface with the coating ink composition produced by the method 100 or 200 according to an embodiment of the present invention will be described.
[0112] The method comprises the steps of applying the coating ink composition on a metal surface (not shown), and forming a graphene coating film on the metal surface by drying or heat-treating the applied coating ink (not shown).
[0113] More specifically, the step of coating the coating ink composition (not shown) can be performed by a coating method selected from dip-coating, doctor-blade coating, slot-die coating and spray coating.
[0114] Here, the graphene coating film may be manufactured by coating the coating ink composition on the metal surface and then drying at 40 to 120° C. for 1 to 20 minutes, or by performing a heat treatment process at 200 to 350° C. for 1 to 20 minutes.
[0115] Furthermore, the thickness of the graphene coating film applied to the metal surface can be easily adjusted by the coating method, coating conditions and the concentration of the coating ink composition.
[0116] The coating ink composition can be easily applied to the surfaces of various metals such as copper (Cu), aluminum (Al), stainless steel (SUS), iron (Fe), nickel (Ni), zinc (Zn), titanium (Ti), and lead (Pb), and can be manufactured into a metal surface graphene coating film with a thickness of tens (nm) to several microns (μm).
[0117] Furthermore, the coating ink composition may further include an organic additive, and the organic additive may include one or more selected from polyacrylamide (Poly(acylamide)), polyvinylidene fluoride (Poly(vinylidene fluoride)), polyvinyl pyrrolidone (Poly(vinyl pyrrolidone)), polymethyl methacrylate (Poly(methyl methacrylate)), polyvinyl acetate (Poly(vinyl acetate)), polyvinyl chloride (Poly(vinyl chloride)), polyvinyl alcohol (Poly(vinyl alcohol)), and polyacrylic acid (Poly(acrylic acid)).
[0118] The organic additive is added and mixed into the coating ink composition, thereby effectively improving the mutual bonding between the graphene nanofilms and the bonding force between the graphene nanofilms and the metal surface, and is easy to be coated on the metal surface.
[0119] Hereinafter, a method 100 and 200 for producing a coating ink composition according to an embodiment of the present invention will be described through specific experimental examples and examples of the present invention. However, these examples are used to exemplify the present invention, and the scope of the present invention is not limited to these production examples and experimental examples.
[0120] [Experimental Example 1]
[0121] first, Figure 3 and Figure 4 2 shows SEM photographs of graphene nanosheets and non-oxidized graphene produced by the method 100 or 200 for producing a coating ink composition according to an embodiment of the present invention.
[0122] Reference Figure 3 and Figure 4 It was confirmed that the expanded graphite (EG) rapidly expanded due to the thermal plasma treatment, and thus the interlayer distance rapidly increased, thereby obtaining graphene nanosheets and non-oxidized graphene powder.
[0123]
Table 1
[0124]
[0125] Figure 6 The graph is a graph of the ink composition produced by the method 100 for producing a coating ink composition according to one embodiment of the present invention measured by a stability analyzer.
[0126] Refer to Table 1. Figure 3 and Figure 6In order to select a suitable polymer that can be used in the method 100 for manufacturing the coating ink composition of the present invention, based on 2 parts by weight of non-graphene oxide, 2 parts by weight of polyvinylpyrrolidone (PVP), 2 parts by weight of polyvinyl alcohol (PVA), 2 parts by weight of polyacrylonitrile (PAN) and 2 parts by weight of polyacrylic acid (PAA) were added respectively, and it was confirmed by a stability analyzer (Turbiscan) that the polyvinylpyrrolidone (PVP) showed the best dispersion stability.
[0127] Furthermore, it was confirmed that in the ink composition other than the one containing polyvinylpyrrolidone (PVP), precipitation occurred rapidly when there was excess polymer.
[0128]
Table 2
[0129]
[0130]
[0131] Figure 7 This is a graph comparing the viscosities of ink compositions produced by the methods 100 and 200 for producing a coating ink composition according to an embodiment of the present invention using a Brookfield viscometer.
[0132] Refer to Table 2 and Figure 7 As shown in Example 1, Example 2 and Comparative Examples 1 to 6, based on 2 parts by weight of graphene nanosheets and 2 parts by weight of non-oxidized graphene, the weight ratio of polyvinylpyrrolidone (PVP) was adjusted to implement synthesis.
[0133]
Table 3
[0134]
[0135] Figure 8 The graph is a graph of the ink composition produced by the method 100 or 200 for producing a coating ink composition according to an embodiment of the present invention measured by a stability analyzer.
[0136] Refer to Table 3 and Figure 8In the case of Example 1, when 2 parts by weight of graphene nanosheets and 10 parts by weight of polyvinylpyrrolidone (PVP) were mixed, the carbon dioxide was 98.6. In the case of Example 2, when 2 parts by weight of non-oxide graphene and 10 parts by weight of polyvinylpyrrolidone (PVP) were mixed, the carbon dioxide was 133.8.
[0137] Hereinafter, the characteristics of the coating ink composition according to one embodiment of the present invention will be described.
[0138] [Experimental Example 2]
[0139] After applying the coating ink composition of the above-mentioned Example 1, Example 2 and Comparative Examples 1 to Comparative Examples 6 of the present invention to the copper metal surface, an active material slurry mixed with LiFePO4, LiCoO2 and LiNiO2 is applied to the coating to manufacture a positive electrode for a secondary battery.
[0140] The interface resistance and adhesion between the coating ink composition and the slurry layer were measured and are shown in Table 4 below.
[0141]
Table 4
[0142]
[0143] Specifically, referring to Table 4, it can be confirmed that when the secondary battery electrodes were produced by applying the coating ink compositions of Examples, Examples 1 and 2 had excellent interface resistance and adhesion between the current collector and the slurry layer containing the active material.
[0144] [Experimental Example 3]
[0145] The effects of the secondary battery separators produced in Example 1, Example 2, and Comparative Examples 1 to 6 were measured by the following method, and the results are shown in Table 5 below.
[0146]
Table 5
[0147]
[0148] 1. Immersion in electrolyte
[0149] A separator having a predetermined size was immersed in an electrolyte containing a lithium salt, and then taken out to measure the weight increase rate of the separator.
[0150] 2. Ionic conductivity
[0151] A separator having a predetermined size was immersed in an electrolyte solution containing a lithium salt, and then attached between two stainless steel (SUS) electrodes, and the ion conductivity was measured.
[0152] 3. Gap blockage
[0153] A separator having a predetermined size was immersed in an electrolyte solution containing a lithium salt, and then the resistance according to temperature was measured (HotER test), and the temperature at which the resistance increased sharply was confirmed.
[0154] 4.Thickness reduction and shrinkage
[0155] After placing a separator having a predetermined size in an oven at 150° C. for 10 minutes, the thickness and the area change of the separator were measured, and the shrinkage rate was calculated.
[0156] Referring to Table 5, the secondary battery separators were clogged at about 140° C., but it was confirmed that the clogged pores in Comparative Examples 1 and 2 occurred very slowly, that is, no effect of suppressing thermal runaway was confirmed.
[0157] It was confirmed that the thickness reduction and the shrinkage rate of Comparative Examples 3 to 6 changed greatly, and it was found that the thermal shrinkage caused a short circuit inside the battery and triggered thermal runaway.
[0158] On the contrary, it was confirmed that in the case of Example 1 and Example 2 of one embodiment of the present invention, no thermal shrinkage occurred, so that no short circuit occurred inside the battery at high temperature, and thermal runaway inside the secondary battery could be prevented.
[0159] It was confirmed from the above-described Production Examples, Experimental Examples, Examples, and Comparative Examples that when an ink composition is produced by the production method of the present invention, an ink composition having excellent dispersion stability can be produced due to its high viscosity.
[0160] The above description of the present application is for illustrative purposes only, and those skilled in the art in the technical field to which the present application belongs will appreciate that the present application can be easily modified into other specific forms without changing the technical concept or essential features of the present application.
[0161] Therefore, it should be understood that the embodiments described above are illustrative in all aspects and not limiting. For example, each component described in a single manner may also be implemented in a dispersed manner, and similarly, components described in a dispersed manner may also be implemented in a combined manner.
[0162] The scope of the present application is shown in the attached patent protection scope rather than the specific description, and all changes or deformations derived from the meaning, scope and equivalent concepts of the patent protection scope should be interpreted as being included in the scope of the present application.
Claims
1. A method for producing a coating ink composition, characterized in that: include: (a) Steps for producing graphene nanosheets using thermal plasma; (b) a step of mixing and stirring a polymer in a solvent to produce a first polymer solution; (c) a step of adding the manufactured graphene nanosheets into the manufactured first polymer solution to manufacture a first graphene solution; (d) a step of subjecting the first graphene solution to high-speed homogenization to produce a second graphene solution; and (e) A step of preparing a coating ink composition containing graphene nanosheets by using the second graphene solution using shear stress of a high-pressure homogenizer.
2. The method for producing a coating ink composition according to claim 1, wherein: The average particle size of the graphene nanosheets is 0.1 μm to 100 μm.
3. The method for producing a coating ink composition according to claim 1, wherein: The solvent is selected from at least one of water, alcohol solvents including ethanol, chloroform, glycerol and acetic acid.
4. The method for producing a coating ink composition according to claim 1, wherein: The polymer is selected from one or more of polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol, polypropylene glycol, polyacrylonitrile and polyacrylic acid.
5. The method for producing a coating ink composition according to claim 1, wherein: The first polymer solution is obtained by mixing the solvent and the polymer at a mixing ratio of 95:5 or 5:1, respectively.
6. The method for producing a coating ink composition according to claim 1, wherein: In the step (c), the graphene nanosheets added to the first polymer solution are in an amount of 0.2 parts by weight to 20 parts by weight based on 100 parts by weight of the first polymer solution.
7. The method for producing a coating ink composition according to claim 1, wherein: Also includes: (f) a step of manufacturing graphene nanosheets using thermal plasma; (g) a step of pulverizing the graphene nanosheets using an air jet mill to produce non-oxidized graphene powder.
8. The method for producing a coating ink composition according to claim 7, wherein: The average particle size of the non-graphene oxide powder is 0.2 μm to 20 μm.
9. A coating ink, characterized in that: The coating ink is produced according to the method for producing a coating ink composition according to any one of claims 1 to 8.
10. A method for coating a metal surface, characterized in that: include: The step of applying the coating ink according to claim 9 on the metal surface; as well as A step of forming a graphene coating film on the metal surface by drying or heat-treating the applied coating ink.
11. The method for coating a metal surface according to claim 10, characterized in that: The step of applying the coating ink is performed by a coating method selected from the group consisting of dipping, blade coating, slot die coating and spray coating.
12. The method for coating a metal surface according to claim 10, characterized in that: The step of forming the graphene coating film is drying at a temperature of 30° C. to 100° C. for 5 to 30 minutes, or heat treating at a temperature of 100° C. to 200° C. for 10 to 120 minutes.
13. A graphene-coated metal material, characterized in that: include: Metal materials; as well as A graphene coating film coated on the surface of the metal material by the method for coating a metal surface according to claim 10.
14. A lithium secondary battery, characterized in that: Contains electrodes, The surface of the current collector of the electrode is coated with the coating ink according to claim 9.
15. The lithium secondary battery according to claim 14, characterized in that: The electrode being coated is the positive electrode and / or the negative electrode.
16. The lithium secondary battery according to claim 14, characterized in that: The lithium secondary battery is a lithium secondary battery for delaying thermal runaway.
Citation Information
Patent Citations
Skin care cosmetic composition comprising cotton rose and manufacturing method thereof
KR1020180086676A